The Passivation Behavior of Carbon Steel Rods of Nepal in Different Media - Bhattarai, J.; Kafle, A.; Bhattarai, N. P. (Journal of Nepal Chemical Society, 2007)
The passivation behavior of carbon steel rods of Nepal is studied in 1 M HCl, 0.5 M NaCl and 1 M NaOH solutions at 25°C, open to air using corrosion tests and electrochemical measurements. The corrosion rate of all the examined steel rods is significantly lower in 1 M NaOH solution (about 10-3 mm/y) than those in 0.5 M NaCl (about 10-2 mm/y) and 1 M HCl (about 101-102 mm/y) solutions. The corrosion rate of SR71 steel rod is remarkably lower (3.65 mm/y) than those of other four different steel rods (3-4 x 102 mm/y) of Nepal in 1 M HCl solution. The ennoblement of the open circuit potentials of all the examined steel rod specimens is clearly observed in 1 M NaOH solution than those in 0.5 M NaCl and 1 M HCl solutions. The open circuit potentials of the steel rods are in the passive potential regions of the iron wire in 1 M NaOH solution. Therefore, steel rods of different companies of Nepal showed significantly high corrosion resistance in 1 M NaOH solution at 25°C. DOI: 10.3126/jncs.v22i0.520 Journal of Nepal Chemical SocietyVol. 22, 2007 pp.34-40